2013
DOI: 10.1073/pnas.1312937110
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acid saturation by gut lactic acid bacteria affecting host lipid composition

Abstract: In the representative gut bacterium Lactobacillus plantarum, we identified genes encoding the enzymes involved in a saturation metabolism of polyunsaturated fatty acids and revealed in detail the metabolic pathway that generates hydroxy fatty acids, oxo fatty acids, conjugated fatty acids, and partially saturated transfatty acids as intermediates. Furthermore, we observed these intermediates, especially hydroxy fatty acids, in host organs. Levels of hydroxy fatty acids were much higher in specific pathogen-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
289
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 318 publications
(300 citation statements)
references
References 30 publications
5
289
1
5
Order By: Relevance
“…MUFAs (namely, oleic acid -C18:1 c9) were present in both waxes at identical amount (~30 µg FA/mg sample); in contrast, PUFAs, namely, eicosapentaenoic acid (EPA: C22:5 n3), were at higher concentrations in Carnauba wax than in the Witepsol one. Since PUFAs are considered to have more potential for toxicity, 48 when compared with SFA, waxes should be carefully inspected regarding toxicological effects, namely, Carnauba wax, which showed a higher content of these FAs. Our results demonstrate a decreased PUFA content in feces in all SLN-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…MUFAs (namely, oleic acid -C18:1 c9) were present in both waxes at identical amount (~30 µg FA/mg sample); in contrast, PUFAs, namely, eicosapentaenoic acid (EPA: C22:5 n3), were at higher concentrations in Carnauba wax than in the Witepsol one. Since PUFAs are considered to have more potential for toxicity, 48 when compared with SFA, waxes should be carefully inspected regarding toxicological effects, namely, Carnauba wax, which showed a higher content of these FAs. Our results demonstrate a decreased PUFA content in feces in all SLN-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of these studies, numerous PUFA-transforming bacteria, such as Butyrivibrio fi brisolvens ( 4 ), Lactobacillus plantarum (20)(21)(22)(23), and Bifi dobacterium breve ( 19 ), have been isolated, and their metabolic pathways of C 18 PUFAs, such as LA and ␣ -linolenic acid, have been revealed. However, the ability to transform C 20 and C 22 PUFAs has not been studied in detail, although there have been several reports that EPA and DHA are hydrogenated in the rumen in vivo ( 26 ) and disappear during incubations in vitro with mixed ruminal microorganisms ( 27,28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, we have revealed that lactic acid bacteria produce unique PUFAs from various C 18 PUFAs through partial biohydrogenation (21)(22)(23). Thus, the biohydrogenation of C 18 PUFAs has been widely studied.…”
Section: Gc-ms Analysismentioning
confidence: 99%
“…at 37°C for 2 h. Lipid extraction was performed as described previously [7]. The extracted lipids were dissolved in 2 mL of methanol and 3 mL of benzene and then methylated with 150 lL of 1% diazomethane at room temperature for 30 min.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…The action of the gut-bacterial fatty acid saturation metabolism modifies the fatty acid composition of the host and is expected to improve human health by altering lipid metabolism, which is related to the onset of metabolic syndrome [7]. Interestingly, the enzymes involved in the gut-bacterial fatty acid saturation metabolism catalyze modification reactions of free fatty acids without CoA or ACP.…”
Section: Introductionmentioning
confidence: 99%